Chemical, Physical and Mineralogical Properties of Atmospheric Particulate Matter in the Megacity Beijing - Schleicher, Nina Jasmin (KIT Scientific Publishing, 2012)
The scope of this work is to develop a comprehensive understanding of the aerosol pollution in the megacity Beijing. The focus lies on the interaction of anthropogenic and geogenic aerosol particles, their spatio-temporal variation, the most important pollution sources as well as the impact of particulate aerosols on human health and the environment. Furthermore, the bioavailable fraction of metal concentrations and the effect of mitigation measures during the 2008 Olympic Games were evaluated.
English
Keywords: Urban aerosols; Single particle analyses; Anthropogenic and geogenic particles; Bioavailable metal concentrations; Mitigation measures